Circular RNA_CNST Promotes the Tumorigenesis of Osteosarcoma Cells by Sponging miR-421. (20th July 2020) - Wang, Ji-Hai; Wu, Xue-Jian; Duan, Yong-Zhuang; Li, Feng
Circular RNAs (circRNAs) act crucial roles in the progression of multiple malignancies including osteosarcoma (OS). But, the underlying mechanisms by which hsa_circ_0017311 (circCNST) contributes to the tumorigenesis of OS remain poorly understood. Our present study aimed to explore the role and mechanisms of circCNST in OS tumorigenesis. The differentially expressed circRNAs were identified by the Gene Expression Omnibus database. The association of circCNST with clinicopathological features and prognosis in patients with OS was analyzed by RNA fluorescence in situ hybridization (FISH) and quantitative real-time polymerase chain reaction (PCR) analysis. 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT), colony formation assays, and a xenograft tumor model were conducted to assess the role of circCNST in OS cells in vitro and in vivo . CircCNST-specific binding with miR-421 was confirmed by FISH, luciferase gene report, and RNA immunoprecipitation assays. As a result, we found that the expression levels of circCNST were dramatically increased in OS tissues and cell lines as compared with the adjacent normal tissues, and it was associated with tumor size and poor survival in OS patients. Knockdown of circCNST repressed cell viability, colony formation, and xenograft tumor growth, while restored expression of circCNST reversed these effects. Furthermore, circCNST was colocalized with miR-421 in the cytoplasm and acted as a sponge of miR-421, which attenuated circCNST-induced proliferation-promoting effects in OS cells by targeting SLC25A3. In conclusion, our findings demonstrate that circCNST promotes the tumorigenesis of OS cells by sponging miR-421, and provides a potential biomarker for patients with OS.